Hemostatic powders for gastrointestinal bleeding: a review of old, new, and emerging agents in a rapidly advancing field - Jiang, Shirley X.; Chahal, Daljeet; Ali-Mohamad, Nabil; Kastrup, Christian; Donnellan, Fergal (Endoscopy International Open, 2022)
Background and study aims Hemostatic powders are increasingly used to address limitations in conventional endoscopic techniques for gastrointestinal bleeding. Various agents exist with different compositions, characteristics, efficacy, and adverse events (AEs). We sought to review existing hemostatic powders, from preclinical to established agents. Methods A literature review on hemostatic powders for gastrointestinal bleeding was undertaken through a MEDLINE search from 2000–2021 and hand searching of articles. Relevant literature was critically appraised and reviewed for mechanism of action, hemostasis and rebleeding rate, factors associated with hemostatic failure, and AEs. Results The most established agents are TC-325 (Hemospray), EndoClot, and Ankaferd Blood Stopper (ABS). These agents have been successfully applied to a variety of upper and lower gastrointestinal bleeding etiologies, in the form of primary, combination, salvage, and bridging therapy. Few AEs have been reported, including visceral perforation, venous embolism, and self-limited abdominal pain. Newer agents include CEGP-003 and UI-EWD, which have shown results similar to those for the older agents in initial clinical studies. All aforementioned powders have high immediate hemostasis rates, particularly in scenarios not amenable to conventional endoscopic methods, but are limited by significant rates of rebleeding. Other treatments include TDM-621 (PuraStat) consisting of a liquid hemostatic agent newly applied to endoscopy and self-propelling thrombin powder (CounterFlow Powder), a preclinical but promising agent.Conclusions Rapid development of hemostatic powders and growing clinical expertise has established these agents as a valuable strategy in gastrointestinal bleeding. Further research will continue to refine the efficacy and applicability of these agents.